1976
DOI: 10.1111/j.1365-2133.1976.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Infantile eczema

Abstract: A 15-17 year follow-up study was conducted on ninety-nine patients who had suffered from infantile eczema. The persistance of the eczema and the occurrence of related conditions were noted. The persistence of eczema was shown to be greater in those patients with a positive family history of eczema and in those who had developed asthma or hay-fever. An attempt was made to see if the persistence of eczema was affected by the position of the child in the family, and some factors provoking relapses were noted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Different epidemiological studies have suggested that eczema is a disease of early onset, usually occurring during the first 2 years of life [16–18], which may persist to adulthood [3, 19]. In support of this assumption, it has been reported that eczema starting in infancy or early childhood in a group of clinical patients have a persistence between 40% and 60% [20–26]. Our population‐based cohort found a lower persistence from age 1‐or‐2 to 18 years (16.9%).…”
Section: Discussionsupporting
confidence: 77%
“…Different epidemiological studies have suggested that eczema is a disease of early onset, usually occurring during the first 2 years of life [16–18], which may persist to adulthood [3, 19]. In support of this assumption, it has been reported that eczema starting in infancy or early childhood in a group of clinical patients have a persistence between 40% and 60% [20–26]. Our population‐based cohort found a lower persistence from age 1‐or‐2 to 18 years (16.9%).…”
Section: Discussionsupporting
confidence: 77%
“…The finding that patients with seuere AD in childhood had persistent and widespread dermatitis as adul!s to a significantly higher degree than those with moderate dermatitis in childhood is in accordance with the results of several other studies (3,7,9,11), but contradicts Vickers's conclusion (10) that no relation exists between severity of AD in childhood and persistent dermatitis in adult life.…”
Section: Prognostic Factors In Adsupporting
confidence: 82%
“…The unfavourable effect of associated BA as well as AR on the prognosis of AD has been reported previously (9,11). In Vickers's study (10) BA, but not AR, was found to influence the prognosis of AD.…”
Section: Prognostic Factors In Admentioning
confidence: 65%
“…19 A majority of the children that participated in our study developed eczema before the age of 4 years. An Australian study suggests that the occurrence of atopic dermatitis reflects genetic differences to which environmental factors contribute.…”
Section: Discussionmentioning
confidence: 99%